Innovation pedagogy - learning through active multidisciplinary methods - Liisa Kairisto-Mertanen; Meiju Räsänen; Jouko Lehtonen; Harri Lappalainen (Universitat Politècnica de València, 2012)
Traditionally, the role of education has been to give knowledge-based readiness, which later would be applied in practice to various innovation processes in working life. Innovation pedagogy introduces how the development of students' innovation skills from the very beginning of their studies can become possible. The core of innovation pedagogy lies in emphasising interactive dialogue between the educational organization, students, and surrounding working life and society. It aims to develop the student's innovation competencies which are the learning outcomes which refer to knowledge, skills and attitudes needed for the innovation activities to be successful. It is defined as a learning approach that defines in a new way how knowledge is assimilated, produced and used in a manner that can create innovations. The purpose of this study is to first present the concept of innovation pedagogy and later give examples of the methods used in Turku University of Applied Sciences to implement this pedagogical concept into the everyday life of the university. Innovation pedagogy has been developed in Turku University of Applied Sciences where it also forms part of the strategy in the university. The multidisciplinary projects of applied research and development respond to the customer needs and are integrated with education in a flexible way.